Anti-Corporate Activism and Collusion: The Contentious Politics of Palm Oil Expansion in Indonesia. Issue 131 (May 2022) - Berenschot, Ward; Dhiaulhaq, Ahmad; Afrizal; Hospes, Otto; Adriana, Rebekha; Poetry, Erysa
Highlights: First-ever large-scale documentation of palm oil conflicts in Indonesia. In 68% of the studied conflicts communities fail to address their grievances. Palm oil conflicts generate a 'rightless' form of collective action. Informalized state institutions foster collusion between powerholders and palm oil companies. This collusion enables companies to suppress protests of communities against land grabbing. Abstract: The rapid expansion of oil palm plantations in Indonesia has generated a large and growing number of protests against palm oil companies over, mainly, access to land. So far, these protests have been mainly studied through scattered case studies, which precludes an understanding and analysis of general patterns. Addressing this challenge, this paper presents the results of the first-ever large-scale collaborative effort to document 150 conflicts between rural Indonesians and palm oil companies in four Indonesian provinces (West Kalimantan, Central Kalimantan, Riau and West Sumatra). With this material this article unpacks trajectories of the anti-corporate activism sparked by the rapid expansion of palm oil plantations, discussing the causes, character of protests, conflict resolution efforts and outcomes of these conflicts. We find that palm oil conflicts generate a particular 'rightless' form of collective action: instead of invoking legal provisions or rights, communities often avoid formal institutions while adopting largely accommodative forms of protest aimed at improving their bargaining position vis-à-vis companies. Despite regular and intense protests often directed at local governments, we find that in 68 percent of the studied conflicts communities fail to address their grievances. We argue that this limited success is not just due to the inadequacies of legal frameworks but also to the way in which Indonesia's informalized state institutions foster collusion between powerholders and palm oil companies. Such collusion has facilitated the repression of protests and undermined the effectiveness of conflict resolution mechanisms.